The SLUGGS survey: chromodynamical modelling of the lenticular galaxy NGC 1023 - Cortesi, Arianna; Chies-Santos, Ana L.; Pota, Vincenzo; Foster, Caroline; Coccato, Lodovico; Mendes de Oliveira, Claudia; Forbes, Duncan A.; Merrifield, Michael R.; Bamford, Steven P.; Romanowsky, A.J.; Brodie, J.P.; Kartha, Sreeja S.; et al. (Oxford University Press, 2016)
Globular clusters (GCs) can be considered discrete, long-lived, dynamical tracers that retain crucial information about the assembly history of their parent galaxy. In this paper, we present a new catalogue of GC velocities and colours for the lenticular galaxy NGC 1023, we study their kinematics and spatial distribution, in comparison with the underlying stellar kinematics and surface brightness profile, and we test a new method for studying GC properties. Specifically, we decompose the galaxy light into its spheroid (assumed to represent the bulge+halo components) and disc components and use it to assign to each GC a probability of belonging to one of the two components. Then we model the galaxy kinematics, assuming a disc and spheroidal component, using planetary nebulae and integrated stellar light. We use this kinematic model and the probability previously obtained from the photometry to recalculate for each GC its likelihood of being associated with the disc, the spheroid, or neither. We find that the reddest GCs are likely to be associated with the disc, as found for faint fuzzies in this same galaxy, suggesting that the disc of this S0 galaxy originated at z ≃ 2. The majority of blue GCs are found likely to be associated with the spheroidal (hot) component. The method also allows us to identify objects that are unlikely to be in equilibrium with the system. In NGC 1023 some of the rejected GCs form a substructure in phase space that is connected with NGC 1023 companion galaxy.